Extracellular matrix as a driver of chronic lung diseases - Burgess,JK; Weiss,DJ; Westergren-Thorsson,G; Wigen,J; Dean,CH; Mumby,S; Bush,A; Adcock,IM (American Journal of Respiratory Cell and Molecular Biology, 2024)
The extracellular matrix (ECM) is not just a 3 dimensional scaffold that provides stable support for all cells in the lungs but is also an important component of chronic fibrotic airways, vascular, and interstitial diseases. It is a bioactive entity that is dynamically modulated during tissue homeostasis and disease, which controls structural and immune cell functions, drug responses, and which can release fragments that have biological activity and that can be used to monitor disease activity. There is a growing recognition of the importance of considering ECM changes in chronic airways, vascular, and interstitial diseases including (i) compositional changes, (ii) structural and organizational changes, and (iii) mechanical changes -and how these impact on disease pathogenesis. Since altered ECM biology is an important component of many lung diseases, disease models must incorporate this factor to fully recapitulate disease-driver pathways and to study potential novel therapeutic interventions. While novel models are evolving that capture some or all of the elements of the altered ECM microenvironment in lung diseases, opportunities exist to more fully understand cell-ECM interactions that will help devise future therapeutic targets to restore function in chronic lung diseases. In this perspective article, we review evolving knowledge about the ECM's role in homeostasis and disease in the lung.